Implementation of Smart Meeting Room Videowall All in One Using Project Management Framework Methodology at PT. Pupuk Sriwidjaja Palembang - Azhari, Muhammad; Febrian, Muhammad; Sutabri, Tata (Yayasan Cita Cendekiawan Al Khwarizmi, 2023)
Smart meeting room is a